2007
DOI: 10.1096/fj.06-7809com
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterols in “rafts”: a better way to regulate membrane thermal shocks

Abstract: Specialized lipid domains (rafts) that are generally enriched in sterols and sphingolipids, are most likely present in cell membranes of animals, plants and fungi. While cholesterol and ergosterol are predominant in vertebrates and fungi, plants possess complex sterol profiles, dominated by sitosterol and stigmasterol in Arabidopsis thaliana. Fully hydrated model membranes of composition approaching those found in rafts of mammals, fungi and plants were investigated by means of solid-state 2H-NMR, using deuter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
118
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 53 publications
10
118
0
2
Order By: Relevance
“…Accordingly, both the clustering in domains of remorin and PIP2;1 were dramatically affected by treatment with cyclodextrin (Raffaele et al, 2009;Li et al, 2012), indicating a major role for sterols in the spatial segregation of these proteins in membrane domains. This treatment also induced an overall increase in acyl chain disorder and a reduction in liquid phase heterogeneity of isolated tobacco PM (Roche et al, 2008), in line with the ability of phytosterols to induce a Lo phase in ternary mixtures of lipids (Beck et al, 2007). Here, we contribute new evidence in support of the developing "membrane raft" concept by revealing a large-range distribution of the steroldependent ordered level of nanoscale assemblies in plant suspension cells.…”
Section: Spatial Distribution and Dynamic Of Pm Heterogeneitysupporting
confidence: 69%
“…Accordingly, both the clustering in domains of remorin and PIP2;1 were dramatically affected by treatment with cyclodextrin (Raffaele et al, 2009;Li et al, 2012), indicating a major role for sterols in the spatial segregation of these proteins in membrane domains. This treatment also induced an overall increase in acyl chain disorder and a reduction in liquid phase heterogeneity of isolated tobacco PM (Roche et al, 2008), in line with the ability of phytosterols to induce a Lo phase in ternary mixtures of lipids (Beck et al, 2007). Here, we contribute new evidence in support of the developing "membrane raft" concept by revealing a large-range distribution of the steroldependent ordered level of nanoscale assemblies in plant suspension cells.…”
Section: Spatial Distribution and Dynamic Of Pm Heterogeneitysupporting
confidence: 69%
“…Other authors also observed the lower ability of b-sitosterol to order phospholipid chains in the fluid phase compared with cholesterol (Beck et al 2007;Bernsdorff and Winter 2003) and, vice versa, to disturb the arrangement in the gel phase (Beck et al 2007). However, these distinct effects of cholesterol or b-sitosterol on d L are not observed in our measurements.…”
Section: Resultsmentioning
confidence: 95%
“…They have been proposed as key molecules to maintain membranes in a state of fluidity adequate for function. For instance, phytosterols have been recently shown to increase membrane cohesion in order to maintain plant membranes in a state of dynamics less sensitive to temperature shocks [6,7]. In this review, the impact of different classes of sterols on membrane dynamics from mammals to archebacteria will be discussed.…”
Section: Introduction: Sterols and The Dynamic Membranementioning
confidence: 99%